Racial and Ethnic Differences in Sociodemographic, Clinical, and Treatment Characteristics Among Patients with Atopic Dermatitis in the United States and Canada: Real-World Data from the CorEvitas Atopic Dermatitis Registry - Jonathan I. Silverberg; Vivian Y. Shi; Andrew Alexis; Evangeline Pierce; Angel Cronin; Robert R. McLean; Carla Roberts-Toler; Maria J Rueda; Amber R. Atwater; Eric Simpson (Adis, Springer Healthcare, 2023)
Abstract Introduction This real-world, cross-sectional study compared sociodemographic, clinical and treatment characteristics, and patient-reported outcomes (PROs) among racial/ethnic groups in patients with atopic dermatitis (AD) who are candidates for systemic therapy. Methods This study included adults with dermatologist- or dermatology practitioner-diagnosed AD enrolled in the CorEvitas AD Registry (July 2020-July 2021). All patients initiated systemic therapy within 12 months prior to or at enrollment or had moderate-to-severe AD (vIGA-AD® ≥ 3 and Eczema Area and Severity Index [EASI] ≥ 12) at enrollment. Patients were categorized into five mutually exclusive racial/ethnic groups: non-Hispanic White, Black, Asian, Other/Multiracial, and Hispanic (any race). Patient, clinical, and treatment characteristics were captured at enrollment. Differences in means or proportions of characteristics among racial/ethnic groups were descriptively summarized using effect sizes. Adjusted prevalence ratios and mean differences were estimated (White race/ethnicity group as the reference category) with 95% confidence intervals (CI). Results Among 1288 patients, 64% (n = 822) were White, 13% (n = 167) Black, 10% (n = 129) Asian, 8% (n = 97) Hispanic, and 6% (n = 73) Other/Multiracial. In adjusted analyses, statistically more severe EASI lichenification was noted among Black compared with White patients at the head and neck (mean difference, 0.21, [95% CI 0.06, 0.36]; p = 0.01), trunk (0.32, [0.17, 0.47]; p < 0.001), upper extremities (0.27, [0.09, 0.44]; p = 0.008), and lower extremities (0.39, [0.21, 0.57]; p < 0.001). Statistically more severe EASI lichenification was observed among Asian vs White patients in certain areas (mean difference, head and neck, 0.22 [0.04, 0.39], p = 0.01; trunk, 0.25 [0.07, 0.43], p < 0.001; lower extremities, 0.22 [0.01, 0.43], p < 0.001) and SCORing for AD lichenification (mean difference: 0.34 [0.15, 0.52]; p < 0.001). Significantly higher mean pruritus over the past 7 days for Black (mean difference: 0.63 [0.01, 1.26] and Hispanic patients (0.60 [0.11, 1.09]; p = 0.03) vs White patients was observed. Among AD clinical features, the prevalence of facial erythema was significantly lower among Black compared with White patients (prevalence ratio = 0.38, [0.22, 0.67]; p = 0.007). Conclusion Racial/ethnic differences exist in sociodemographic, clinical and treatment characteristics, disease severity, and PROs among real-world AD patients who are candidates for systemic therapy. Recognizing these variations may be of critical importance for dermatologists for the design and delivery of targeted/personalized medicine approaches.